Pacing strategies in the New York City Marathon - Does nationality of finishers matter? - Aschmann, A.; Knechtle, B.; Onywera, V.; Nikolaidis, P. T. (Asian Journal of Sports Medicine, 2018)
Previous research has indicated that sex, age and performance level of finishers influence pacing strategies in the marathon. However, the variation of pacing by country of origin and/or nationality of finishers has not been studied. The aim of this study, therefore, was to examine whether runners with different nationality differ in their pacing strategies. Data (women, n = 117,595; men, n = 180,487) from the `New York City Marathon` between 2006 and 2016 were analysed. A small main effect of nationality on age was shown (P < 0.001, Eta2 = 0.032) with Ethiopians being the youngest (30.2 ± 8.4 years) and Japanese the oldest (45.1 ± 10.9 years). A trivial main effect of nationality on race time was shown (P < 0.001, Eta2 = 0.008) with Ethiopians (2:49:24 ± 0:49:17 h:min:s) and Kenyans (3:08:34 ± 1:05:46 h:min:s) being the fastest and Japanese the slowest (4:30:43 ± 0:54:37 h:min:s). A trivial split × nationality interaction on race speed was observed in women (P < 0.001, Eta2 = 0.004) and men (P < 0.001, Eta2 = 0.005) with Ethiopians and Kenyans showing more even pacing strategies than the other nationalities (P < 0.001, Eta2 = 0.003; P < 0.001, Eta2 = 0.004, respectively). Accordingly, the largest prevalence of end spurt (women, Chi2 = 646.2, P < 0.001, Phi = 0.074; men, Chi2 = 1163.2, P < 0.001, Phi = 0.080) was found in U.S.-Americans in women (87.2%) and men (78.2%), whereas the smallest was in Ethiopians (54.3%) and Kenyans (45.8%), respectively. Based on these findings, it was concluded that nationality plays a role on marathon runners` pacing, which might be attributed to differences in performance level among nationalities and running tactics.